MICROBIOLOGICAL QUALITY OF PASTEURIZED MILK TYPE B MARKETED IN CURITIBA, PR - Shirai, Marianne Ayumi (2013)
The aim of this work was to evaluate the microbiological quality of pasteurized milk type B marketed in Curitiba city, state of Paraná, Brazil, during his shelf-life. The samples were collected randomly in commercial establishments when they were placed on the shelf and the count of mesophilic, psychrotrophic, proteolytic and lipolytic psychrotrophic microorganisms and determination of alkaline phosphatase and peroxidase were done. The milk samples were cold stored (5ºC) and a new microbiological count was done in the end of shelf life. The results show that during the period of validity, there was an increase in the count of mesophiles in 4 samples. In 7 samples there was multiplication of psychrotrophic.